An Organizational Resilience Potential Scale within the Hospitality Industry in the face of the COVID-19 in Poland - Tomasz EWERTOWSKI (Communications of International Proceedings, 2020)
The hotel industry turned out to be severely affected by the COVID-19. Reopening the Polish hotel industry after government restrictions, provides an opportunity to analyze the individual strategies taken by hotels to maintain their operational capabilities. Against this background, resilience as a risk measure used to assess the performance of an organization plays a very important role. The article proposes the Organizational Resilience Potential Scale for assessing the potential of resilience measures such as: redundancy, resourcefulness and rapidity. Additionally, four sub-measures related to the key resilience capabilities of the organization were identified. The survey was based on the questionnaire consisting of 22 questions to measure the potential of resilience. The results of the analyses were referred to risk matrices for individual measures to qualify them to a specific risk category, allowing managers to find out what aspects need to be taken into account to increase the resilience of the organization.
Keywords: Organizational Resilience; Hospitality Industry; Crisis Management.